COMPOSITE PRODUCTS BASED ON IRON POWDER WITH INCREASED PHYSICAL AND MECHANICAL PROPERTIES - Гальчук, Тетяна (SWorldJournal, 2025)
The paper considers the possibility of manufacturing and using sintered composite products from metal powders of iron and copper. Research was carried out under optimal parameters of pressing pressure, temperature and sintering time. It has been experime